Numerical study of the influence of tube arrangement on the flow distribution in the header of shell and tube heat exchangers. (5th November 2017) - Labbadlia, O.; Laribi, B.; Chetti, B.; Hendrick, P.
Highlights: The influence of tubes arrangement on the flow distribution has been investigated. Four arrangements types, in a shell and tube heat exchanger, have been studied. Tubes arrangement type directly affect the flow distribution. The 45° arrangement ensures a high velocity at maximum number of tubes. The 60° arrangement provides the best flow distribution uniformity. Abstract: The behavior of the fluid inside the internal circulation system of a shell and tube heat exchanger is complex due to the influence of many factors. The flow distribution has a significant influence on the performance of fluidic apparatus such as shell and tube heat exchangers. The non-uniformity of the flow distribution reduces the efficiency of the process. The influence of tubes arrangements on the flow distribution is presented using CFD simulations. In this study, four arrangement types are considered. The present results are in good agreement with those of the literature. The obtained results show that the arrangement of the tubes has a significant influence on the flow distribution. It was concluded that the flow distribution of 60° arrangement exhibits better uniformity compared to the conventional arrangement (90°) by 21%. The 45° arrangement gives good uniformity of pressure distribution compared to the other arrangements.